Swiss roll - Varma, J. R. (Jayanth R.); Virmani, Vineet (London : Indian Institute of Management, Ahmedabad, 2016)
On 15 January 2015, Thomas Jordan, Chairman of the Board of Governors of the Swiss National Bank was forced to call an emergency meeting to take stock of the developing monetary situation in Switzerland, and decide the course of monetary policy in the immediate future. For more than three years, the principal anchor of its monetary policy had been the exchange rate floor of 1.20 Swiss franc to the euro introduced in September 2011. Domestic and international developments during the last few months had placed enormous strain on the central bank, and its actions at the planned meeting would be critical.
Originally published in Varma, J. R., & Virmani, V. (2016). Swiss Roll. F&A0532(A). Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Jordan, Thomas J; Schweizerische Nationalbank; Banks and banking, International